PENGEMBANGAN MEDIA GAMBAR BERSERI BERBASIS POP-UP BOOK UNTUK MENINGKATKAN KEMAMPUAN BERBICARA KELAS II SEKOLAH DASAR - Andara Sintho Retnoningtya; Alfi Laila; Rian Damariswara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research and development is to determine the level of validity, practicality and effectiveness of pop-up book-based serial picture learning media to improve speaking skills in class II elementary schools. The research method used is R & D (Research and Development) with the ADDIE model which consists of 5 steps, namely (1) Analysis, (2) Design (design), (3) Development (development), (4) Implementation (implementation) , (5) Evaluation (Evaluation). The results of this research show that. (1) The validation results obtained from the media validator reached a percentage of 96% and the material validator reached 88%, so the validation results are included in the very valid criteria. (2) The results of the limited scale teacher response questionnaire were 96%, the broad scale teacher response was 94% and the results of the limited scale student response questionnaire were 98%, the results of the broad scale student questionnaire were 97%, reaching very good criteria, so the practicality of pop-up book-based serial picture learning media wisdom has very practical criteria. (3) the results of the effectiveness test on a limited scale obtain a normality test value of sig. of 0.942 > 0.005 and 0.499 > 0.05, the data is normally distributed, on a broad scale the normality test results get a value of 0.136 > 0.05 and 0.291 > 0.05, the data is normally distributed, the homogeneity test gets a value of 0.053 > 0.05, so the data is the same or homogeneous, the t-test gets a sig value. (2-tailed) obtained is 0.000 < 0.05, so there is a difference between the post-test and pre-test, which means there is an influence of the use of pop up book serial image learning media on improving student learning.